2007
DOI: 10.1269/jrr.06032
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Effects of Hawthorn Fruit Extract Against Gamma Irradiation in Mouse Bone Marrow Cells

Abstract: The radioprotective effect of hawthorn (Crataegus microphylla) fruit extract against genotoxicity induced by gamma irradiation has been investigated in mouse bone marrow cells. A single intraperitoneal (ip) administration of hawthorn extract at doses of 25, 50, 100 and 200 mg/kg 1h prior to gamma irradiation (2 Gy) reduced the frequencies of micronucleated polychromatic erythrocytes (MnPCEs). All four doses of hawthorn extract significantly reduced the frequencies of MnPCEs and increased the PCE/PCE+NCE ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Ionizing irradiation can induce DNA damage and cell death by generating ROS (Schmidt-Ullrich et al 2000). An increased understanding of the relationship between the effects of oxygen and irradiation exposure has led to increased interest in natural antioxidants due to their multiply effective potency and low toxicity (Davis et al 2007;Hosseinimehr et al 2007). In this study, we demonstrated the ability of THP to prevent and reduce irradiationinduced damage at a cellular level in the human endothelial cell line EA.hy926.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Ionizing irradiation can induce DNA damage and cell death by generating ROS (Schmidt-Ullrich et al 2000). An increased understanding of the relationship between the effects of oxygen and irradiation exposure has led to increased interest in natural antioxidants due to their multiply effective potency and low toxicity (Davis et al 2007;Hosseinimehr et al 2007). In this study, we demonstrated the ability of THP to prevent and reduce irradiationinduced damage at a cellular level in the human endothelial cell line EA.hy926.…”
Section: Discussionmentioning
confidence: 74%
“…Consequently, drugs of herbal origin have gained increasing attention recently as potential radioprotective agents due to their pharmacological properties and low toxicity (Hosseinimehr et al 2007). Rhizoma corydalis is a Chinese herbal medicine of fundamental importance which has been traditionally used to help invigorate the blood, move qi, reinforce vital energy and alleviate pain (Ding 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Leaves, fruits Antibacterial, antifungal, antiviral, antidiabetic [33] C. tanacetifolia Leaves Hypotensive, antimicrobial [53] C. pentaegyna Fruits Antioxidant [45] C. microphylla Fruits Radioprotective [54] C. sinaica Fruits, leaves Antiviral, including anti-HIV; antioxidant; anticomplementary [55] Crataegus spp. Fruits, leaves Diuretic/ACE inhibitor [41] C. azarolus var.…”
Section: Root Infusion Leavesmentioning
confidence: 99%
“…It appeared that hawthorn extract exhibits antioxidant activity and reduced the genotoxicity induced by gamma radiation in mouse bone marrow cells. Phytochemical study revealed that C. microphylla contains high amounts of phenolic compounds, chlorogenic acid, hyperoside and epicatechin which might be responsible for its radioprotective potential (Hosseinimehr et al, 2007).…”
Section: Radioprotective Activitymentioning
confidence: 99%